2015
DOI: 10.1111/nph.13257
|View full text |Cite
|
Sign up to set email alerts
|

HbNIN2, a cytosolic alkaline/neutral‐invertase, is responsible for sucrose catabolism in rubber‐producing laticifers of Hevea brasiliensis (para rubber tree)

Abstract: Summary In Hevea brasiliensis, an alkaline/neutral invertase (A/N‐Inv) is responsible for sucrose catabolism in latex (essentially the cytoplasm of rubber‐producing laticifers, the source of natural rubber) and implicated in rubber yield. However, neither the gene encoding this enzyme nor its molecular and biochemical properties have been well documented. Three Hevea A/N‐Inv genes, namely HbNIN1, 2 and 3, were first cloned and characterized in planta and in Escherichia coli. Cellular localizations of HbNIN2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 64 publications
(124 reference statements)
1
52
0
4
Order By: Relevance
“…The roles of VI in the major regulation of carbon metabolism, hexose distribution, cellular osmolarity, and oxidative stress defense have been extensively explored (Kohorn et al , 2006; Sergeeva et al , 2006; Nägele et al , 2010; Xiang et al , 2011; Liu et al , 2015). Suppression of VI activities alters soluble sugar conversion, thereby decreasing cold-induced sweetening in potato tubers (Bagnaresi et al , 2008; Bhaskar et al , 2010; Zhu et al , 2016) and affecting fruit size (Klann et al , 1996; Tang et al , 1999; Yu et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The roles of VI in the major regulation of carbon metabolism, hexose distribution, cellular osmolarity, and oxidative stress defense have been extensively explored (Kohorn et al , 2006; Sergeeva et al , 2006; Nägele et al , 2010; Xiang et al , 2011; Liu et al , 2015). Suppression of VI activities alters soluble sugar conversion, thereby decreasing cold-induced sweetening in potato tubers (Bagnaresi et al , 2008; Bhaskar et al , 2010; Zhu et al , 2016) and affecting fruit size (Klann et al , 1996; Tang et al , 1999; Yu et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
“…NI regulates sucrose metabolism in many plants, including Saccharum officinarum, Beta vulgaris, and Citrus reticulata (Hubbard et al, 1991), and plays an important role in monosaccharide-dependent biosynthesis (Nonis et al, 2007). In order to investigate the role of NI in polysaccharide-synthesis regulation, several NI cDNAs have been cloned from Solanum lycopersicum, Hevea brasiliensis, Saccharum officinarum, and Oryza sativa (Gallagher and Pollock, 1998;Murayama and Handa, 2007;Bocock et al, 2008;Liu et al, 2015), and differential NI expression has been reported in different plant tissues, e.g., in tomato, higher mRNA levels have been detected in the fruit and leaves than in the flowers and stems. In contrast, in Hevea brasiliensis, the highest mRNA levels were detected in the bark and leaves.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the development of molecular biology makes the studies of gene expression and regulation related to natural rubber biosynthesis become a hotspot in undressing the mechanisms of latex regeneration. For instance, several researchers have focused on the genes involved in the supply and utility of sucrose in the latex, using gene expression profile especially qPCR analysis (Dusotoit-Coucaud et al, 2010;Tang et al, 2010;Liu et al, 2015). To reveal the underlying molecular mechanism and regulatory network of latex regeneration, it is necessary and crucial to screen the suitable reference genes for normalization in relevant gene expression analysis.…”
Section: Introductionmentioning
confidence: 99%